Respuesta :

Answer:

x = -9/2

Step-by-step explanation:

64 = 2^6

if you have the same base, you can set the exponents equal and solve for x.

-2x-3 = 6

-2x = 9

x = -9/2

good luck on your final! you got this!

Step-by-step explanation:

[tex] {2}^{ - 2x - 3} = 64[/tex]

first, get 64 to a base of 2

[tex] {2}^{ - 2x - 3} = {2}^{6} [/tex]

now we can drop the bases

[tex] - 2x - 3 = 6[/tex]

And now we can solve it like any other equation

[tex] - 2x = 6 + 3[/tex]

[tex] - 2x = 9[/tex]

[tex]x = - \frac{9}{2} [/tex]

ACCESS MORE